Chemical characterization and reactivity of iron chelator-treated amphibole asbestos. - Gold, J (1997)
Iron in amphibole asbestos is implicated in the pathogenicity of inhaled fibers. Evidence includes the observation that iron chelators can suppress fiber-induced tissue damage. This is believed to occur via the diminished production of fiber-associated reactive oxygen species. The purpose of this study was to explore possible mechanisms for the reduction of fiber toxicity by iron chelator treatments. We studied changes in the amount and the oxidation states of bulk and surface iron in crocidolite and amosite asbestos that were treated with iron-chelating desferrioxamine, ferrozine, sodium ascorbate, and phosphate buffer solutions. The results have been compared with the ability of the fibers to produce free radicals and decompose hydrogen peroxide in a cell-free system in vitro. We found that chelators can affect the amount of iron at the surface of the asbestos fibers and its valence, and that they can modify the chemical reactivity of these surfaces. However, we found no obvious or direct correlations between fiber reactivity and the amount of iron removed, the amount of iron at the fiber surface, or the oxidation state of surface iron. Our results suggest that surface Fe3+ ions may play a role in fiber-related carboxylate radical formation, and that desferrioxamine and phosphate groups detected at treated fiber surfaces may play a role in diminishing and enhancing, respectively, fiber redox activity. It is proposed that iron mobility in the silicate structure may play a larger role in the chemical reactivity of asbestos than previously assumed.